Natural Product Goniothalamin Induced NADPH-Diaphorase Expression in the Liver: A Possible Role of Nitric Oxide in Hepatoprotection - Yap, Hui Man; Albalawi, Abdalaziz Faleh; Alhussain, Naif Hussain; Alharbi, Abdullah Hamdan; Ibrahim, Morizeeq Ahamed; Seyed, Mohamed Ali (Indian Journal of Pharmaceutical Education and Research, 2025)
Background/Aim Goniothalamin (GTN) has received significant attention for its selective cytotoxicity toward multiple tumor cell lines, without causing any effect on normal cells. Despite a lack of toxicity, the poor potency of GTN hinders its clinical development. The existing in vivo data are also insufficient to support that GTN does not have effect on healthy cells. This prompted us to investigate whether GTN may produce any changes on healthy cells in the organs of mice especially liver as it is vital for metabolism of drugs. The present study aimed to examine the effects of Goniothalamin (GTN), one of the emerging plant-derived anticancer metabolites on the morphology of mouse liver and its possible role in the expression and distribution of Nicotinamide Adenine Dinucleotide Phosphate Diaphorase (NADPH-d), an indirect indicator of Nitric Oxide Synthase (NOS). Materials and Methods Mice were randomly assigned to four main groups (n=72): Experimental group (GTN), positive control group (Betulinic acid; BetA), vehicle control group (Dimethyl Sulfoxide; DMSO) and control group (without vehicle). They were further classified into three sub-groups as per the treatment period like 4-day, 8-day and 12-day. Results The NADPH-d expression indicates the presence of NOS, which is an enzyme that involves in the formation of Nitric Oxide (NO). Our results revealed that GTN treatment induced NADPH-d activity in the liver with no significant morphological changes. Furthermore, the expression of NADPH-d significantly increased in the GTN-treated group, when compared to other groups. The NADPH-d positive portal triads, sinusoids and nerve fiber like structures may suggest the role of NO in regulating the blood flow and maintaining the function of liver cells. The distribution of NO in the portal tract suggests the role of NO in transporting bile and the NO detected in hepatocytes may indicate either normal development or to some extent of injury in the hepatic cells. The total surface area stained on the entire surface of the liver lobule was calculated using FIJI software and the results were analyzed by GraphPad software. The stained areas in the test group did not show significant difference when compared to the stained areas in control group. Conclusion NADPH-d expression in the liver of mice suggests that NO signaling may play a key role in GTN-induced hepatoprotection. These results are of direct clinical importance and may pave the way for further development of GTN as a potential pharmaceutical candidate.
Keywords: NADPH-d; Nitric oxide; Goniothalamin; Betulinic acid; Mice; Liver